International Law : A Very Short Introduction - Lowe, A. V. (Alan Vaughan) (Great Clarendon Oxford University Press, 2015)
This title provides students with a concise and analytical overview of what the 'law' means in an international context and an introduction to the main institutions and mechanisms of international law.
Include Illustrations and Index